Analysis of Approaches in the Microsurgical Treatment of 102 Cases of Petroclival Meningioma in a Single Center - Lin, Yazhou; Gao, Qiang; Jin, Huiping; Wang, Nana; Xu, Dingkang; Wang, Fang; Guo, A. Bao; Zang, Weidong; Li, Zhihua; Guo, Fuyou (Frontiers in Neurology, 2021)
Objectives: We identified the optimal approaches for treating the diverse tumour subtypes of petroclival meningioma (PM) by analysing the clinical benefits of various surgical approaches adopted for each subtype. Methods: Tumours in 102 PM patients from a single centre who underwent surgical treatment were classified as upper clivus (UC), cavernous sinus (CS), tentorium (TE), or petrous apex (PA) types based on the attachment site of the tumour base and the displacement of the trigeminal nerve. The therapeutic effects of different surgical approaches among the subtypes were evaluated according to the patient outcomes. Results: The subtemporal (33.33%), retrosigmoid (16.67%), and Kawase approaches (50%) were used for the UC type. Simpson I/II resection was achieved in 46.66% of patients with the Kawase approach. Significant differences were found between the other two approaches (P=0.044) and in the follow-up Karnofsky performance scale (KPS) scores (P=0.008). The subtemporal (60%) and Kawase approaches (40%) were used for the CS type; neither approach achieved Simpson I/II resection. The retrosigmoid (25.81%) and Kawase approaches (74.19%) were used for the TE type. The Simpson I/II resection rates of the two approaches were 55.55% and 86.95%, respectively, and a significant difference was observed between them (P=0.039). The retrosigmoid (43.75%) and Kawase approaches (56.25%) were used for the PA type. The Simpson I/II resection rates of the two approaches were 31.25% and 50%, respectively. The resection degrees of the two approaches and the KPS scores at follow-up were significantly different (P=0.034). Conclusion: The individual microsurgical approaches adopted for the various PM tumour subtypes can provide maximal safe resection and good KPS scores. The Kawase approach is more suitable for PM, especially for UC- and PA-type PM tumours.